DIFFUSIVITY IN SURFICIAL SEDIMENTS AND BENTHIC MATS DETERMINED BY USE OF A COMBINED N2O-O2 MICROSENSOR - Glud R.N.; Jensen K.; Revsbech N.P. (My University, 1995)
Diffusional characteristics of two biologically active surface sediments were determined by use of a combined N2O-O2 microsensor. By analyzing changes in the N2O-gradients in these sediments, it was possible to determine the product (φDs) for this species with submillimetre depth resolution, where φ is the porosity and Ds the substrate diffusion coefficient. The (φDs)-value for O2 could be calculated then from (φDs)-values for N2O, because the diffusivity of the two molecules were modified in the same way within the sediment. Both sediments exhibited fine-scale horizontal and vertical variability in diffusion characteristics, and this must be accounted for when analyzing microprofile data. The average (φDs)-value for N2O at 20°C for an estuarine surface sediment was 0.93 x 10-5 cm2 s-1 (at 0-4 mm depth), while the value for the upper 2 mm of a stream sediment covered by a microbial mat was 1.42 x 10-5 cm2 s-1. Biological inactivation and oxidation by exposure to an O2 atmosphere had no effect on the measured (φDs) for the estuarine sediment; however, the value for the sediment covered by a microbial mat, with dense populations of meiofauna, decreased by 20%. The method presented is ideal for measurements of diffusivity at a high spatial resolution in surficial sediments and densely packed microbial communities.